Friendly sovereignty : historical perspectives on Carl Schmitt's neglected exception - Miller, Ted H., 1965- (The Pennsylvania State University Press, 2022)
"Explores the diverse views of Jules Michelet, Thomas Hobbes, and Seneca on the extralegal aspects of sovereign prerogative power, often associated with grace, favor, leniency, and pardons"--